2018
DOI: 10.1002/app.46405
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and water absorption behaviors of corn stalk/sisal fiber‐reinforced hybrid composites

Abstract: In this study, corn stalk flour (CSF) was used as filler instead of wood flour (WF) to prepare poly(vinyl chloride) (PVC) based wood plastic composite (WPC). In order to enhance the mechanical properties of the WPC, sisal fiber (SF) was introduced as reinforcer. The mechanical and the water absorption behaviors of WPC were investigated in detail. The results indicated that the chemical structure of CSF proved by FTIR was similar to that of WF. The effect of the hybridization of SF and CSF on the mechanical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The work on corn stalk/sisal fiber hybrid composites was carried out and found that hybridization has improve the mechanical behavior of the composites. [ 118 ] The hybrid sisal/OPEBF/rubber composites produced and their mechanical properties were studied. [ 119 ] The results showed that highly concentrated enriched fibers were registered improved modulus and decreased tensile and shear strengths.…”
Section: Effect Of Hybridization On Propertiesmentioning
confidence: 99%
“…The work on corn stalk/sisal fiber hybrid composites was carried out and found that hybridization has improve the mechanical behavior of the composites. [ 118 ] The hybrid sisal/OPEBF/rubber composites produced and their mechanical properties were studied. [ 119 ] The results showed that highly concentrated enriched fibers were registered improved modulus and decreased tensile and shear strengths.…”
Section: Effect Of Hybridization On Propertiesmentioning
confidence: 99%
“…Giridharan [26] evaluated hybrid ramie/glass fiber (20%/80% and 30%/70%), epoxy composites by tensile, flexural and impact tests and found that the hybrid composites (30%/70%) exhibited better mechanical properties than non-hybrid composites. Chen et al [27] examined the mechanical and water absorption behaviors of corn stalk/sisal fiber hybrid composites. It was showed that the hybridization with sisal fiber significantly enhanced the mechanical properties (flexural strength increased by 20% and tensile strength by 49.5%) but had little effect on water absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Plant fiber reinforced polymer composites (PFRPs) are biomaterials prepared by using plant fibers as reinforcement material and thermoplastics as matrix. Such composites have been widely applied in structural and construction areas, such as decking and fencing (Ku et al 2011;Leu et al 2012;Chen et al 2018). Nevertheless, the hydrophilic character of plant fibers has caused some cases of PFRPs failures in outdoor service, especially in high humidity environments.…”
Section: Introductionmentioning
confidence: 99%